CHK1-CDC25A-CDK1 regulate cell cycle progression and protect genome integrity in early mouse embryos - Knoblochova, Lucie; Duricek, Tomas; Vaskovicova, Michaela; Zorzompokou, Chrysoula; Rayova, Diana; Ferencova, Ivana; Baran, Vladimir; Schultz, Richard M; Hoffmann, Eva R; Drutovic, David (EMBO reports, 2023)
After fertilization, remodeling of the oocyte and sperm genomes is essential to convert these highly differentiated and transcriptionally quiescent cells into early cleavage-stage blastomeres that are transcriptionally active and totipotent. This developmental transition is accompanied by cell cycle adaptation, such as lengthening or shortening of the gap phases G1 and G2. However, regulation of these cell cycle changes is poorly understood, especially in mammals. Checkpoint kinase 1 (CHK1) is a protein kinase that regulates cell cycle progression in somatic cells. Here, we show that CHK1 regulates cell cycle progression in early mouse embryos by restraining CDK1 kinase activity due to CDC25A phosphatase degradation. CHK1 kinase also ensures the long G2 phase needed for genome activation and reprogramming gene expression in two-cell stage mouse embryos. Finally, Chk1 depletion leads to DNA damage and chromosome segregation errors that result in aneuploidy and infertility.
Keywords: CHK1 kinase; CDC25A phosphatase; CDK1 kinase; cell cycle regulation; early mouse embryos